Empirical analysis of the influence of voters and politicians in the public choice of Portuguese municipalities universidade portucalense - José Manuel Cruz (European Regional Science Association (ERSA), 2004)
When estimating a specification combining different influences on local public choice, three public issues of different ideological attributes were compared for two periods of Portuguese local government intervention: the beginning and the ending of one electoral cycle. The most exciting results of the paper are the significance of ideology at local level and the decline of its importance in the ending of the electoral cycle. There is also some evidence on the political influence of interest groups, especially in low visible issues. On the general issue, majority is also influent and fiscal illusion is found. Some preliminary panel data results including two electoral cycles are analyzed. JEL CLASSIFICATION: H42; H73; R51 KEYWORDS: Median Voter; Interest Groups; Ideology; Local Government, Opportunistic Political Cycle
Keywords: H42; H73; R51; 330; Median Voter; Interest Groups; Ideology; Local Government; Opportunistic Political Cycle